Analysis of Relationship between Commitment to Civic Engagement and Socio-Psychological Characteristics of Students - Egor V. Nevsky (Saratov State University, 2020)
The purpose of the study presented in the article is to identify the relationship between commitment to civic engagement and socio-psychological characteristics of the individual. The study was carried out on a sample of young students (N = 110) aged 17 to 29 years (M = 23, SD = 3.98), 29% of men and 71% of women. The following methodological tools were used: a questionnaire aimed at fixing the socio-demographic characteristics of respondents; a questionnaire, including a scale of self-assessment of social activity and forms of its manifestation (R. M. Shamionov, I. V. Arendachuk, E. E. Bocharova, etc.); questions aimed at self-assessment of trust in the government institution in the possibility of realizing one's own rights and freedoms; "Personal value questionnaire" by S. Schwartz (PVQ-R2) to study the expression of individual values. Presumably, there is a relationship between the severity of civil society and socio-political forms of activity, trust in institutional sources and values of openness to change. We discovered that the most preferred forms of social activity of young people are leisure, Internet network, spiritual and educational development. Young people are more likely to express confidence in their relatives or friends, and various Internet sources when exercising their rights and freedoms. We demonstrated that participation of young people in activities aimed at transforming society and expressing their own and collective civic position on issues of public life expands the possibilities of achieving personal professional, career and economic goals, as well as the realization of their cultural, national, religious interests, subject to the manifestation of trust in various governing institutions that implement the functions of ensuring the rights and freedoms of a person. Realization of civic activity is associated with desire for novelty and changes in society, on the one hand, the desire for change leads to generation of civic activity associated with transformation of society on the other hand. The value of "stimulation" is a predictor of civic activity. The study of this problem can be applied in work with young people in public municipal organizations, schools, institutes.